Politics and society in Hannah Arendt - Vahí Serrano, Ángel (Differenz. Revista internacional de estudios heideggerianos y sus derivas contemporáneas, 2022)
Controversy about relation between society and politics in Hannah Arendt's thought is focused on by the following reflection. Possibility and chance are argued to defend Arendt's political conception as a way to face the main current challenges, not only political, but social too. Through kantian capacity of Judgement, it is maintained a reciprocal relationship between politics and education that would allow mutually to enrich one another and to give both of them a main role in a humanist way to approach our lives.